The Impact of the New Capital Adequacy Requirement on the Nigerian Banking System - George, Dorcas (2007)
In today's dynamic and complex financial system, safety and soundness can mainly be achieved through efficient management of banks, market discipline and effective prudential supervision. Most emerging economies like Malaysia, Turkey, Nigeria and others have been undergoing series of profound reforms in their financial sector. The common characteristics of these countries that have necessitated the reforms are as a result of financial instability and weak or fragile financial system. One of the recent banking reforms in Nigeria in July 2004 mandated an upward review of the minimum capital which was for the purpose of strengthening the banks and gaining stability in the financial sector.